Over 300 Radiation Caries Papers: Reflections From the Rearview Mirror - Caique Mariano Pedroso; Cesar Augusto Migliorati; Joel B. Epstein; Joel B. Epstein; Ana Carolina Prado Ribeiro; Thaís Bianca Brandão; Márcio Ajudarte Lopes; Mário Fernando de Goes; Alan Roger Santos-Silva (Frontiers Media S.A., 2022)
Radiation caries (RC) is an aggressive oral toxicity in head and neck cancer survivors, which develops 6 to 12 months after head and neck radiotherapy. It initially affects the tooth cervical/incisal surfaces, and if not promptly diagnosed/managed, progresses to dental crown amputation and risk of osteoradionecrosis. It results from a multidimensional cluster of treatment-induced oral symptoms, including hyposalivation, dietary changes, and oral hygiene impairment. Although recognized as a frequent complication of radiotherapy and extensively assessed by a myriad of retrospective, in vitro, and in situ studies, RC patients are still orphans of clinically validated methods for risk prediction, prevention, and treatment of early lesions. This review provides a historical overview of science-based concepts regarding RC pathogenesis and treatment, emphasizing the growing demand for interventional clinical studies (randomized trials).